Relationship of ABO Blood Groups with Fasting Blood Sugar and Uric Acid among Students in Bayelsa State College of Health Technology Otuogidi-Ogbia - Reuben Idaye; Orutugu Lemmy Ayibatonye; Asaba Henry Perezide (International Blood Research & Reviews, 2026)
Background: Evidence concerning the relationship of ABO blood groups with metabolic markers remains inconsistent, particularly among apparently healthy young adults. Aim: To determine the relationship between ABO blood groups, fasting blood glucose, and serum uric acid levels among students of Bayelsa State College of Health Technology. Study Design: An analytical cross-sectional study. Place and Duration of Study: Bayelsa State College of Health Technology, Otuogidi-Ogbia, between January and April 2026. Methodology: In this study, 300 students aged 16–40 years were recruited using Cochran’s formula for sample-size determination. ABO blood grouping was performed using the tile method, fasting blood glucose was measured using a glucose oxidase-based glucometer, and serum uric acid was determined using the uricase enzymatic method. Data were analysed using one-way ANOVA and t-tests in SPSS version 25, with p0.05). Conclusion: ABO blood group was not significantly associated with fasting blood glucose or serum uric acid levels in this student population, suggesting that blood group is not a major independent determinant of glycaemic or uric acid status.